María Alejandra González Pérez. Una investigadora de aquí, de allá, de todas partes (2021)
Santa Teresa used to say that life is an instant between two eternities and, as if she believed in that, María Alejandra González has taken it upon herself to live hers with an intensity that would have already exhausted others. The winner of the 2021 Discovery and Creation Award, she could be a nun, a psychologist or stay until old age in Ireland, she loves dogs and believes in the dignifying role of work.